A new species of Stigmaeus Koch (Acari: Stigmaeidae) from Northwest of Iran - Irani-Nejad, Karim H.; Bagheri, Mohammad; Khanjani, Mohammad; Kamali, Karim; Saboori, Alireza (Zootaxa, 2006)
A new species of Stigmaeus Koch (Acari: Stigmaeidae), S. malekii Haddad, Bagheri & Khanjani, is described and illustrated from Northwestern (East Azarbaijan) Iran. The materials of new species were collected from apple litter. A key to the species of Stigmaeus found in Iran is given.